STATISTICS OF COMPETITION OF SMALL BUSINESS AND PRIVATE ENTREPRENEURS ASSESSMENT METHODS (Euro-Asia Conferences, 2021)
This article provides an analysis of the competitiveness of small business and private entrepreneurship in the country, the definition of competitiveness in the regions of the country, the analysis of key indicators of small business and private entrepreneurship, the restructuring of small businesses, small ensuring the competitiveness of business and private entrepreneurship.